2007
DOI: 10.1158/0008-5472.can-07-2041
|View full text |Cite
|
Sign up to set email alerts
|

PCPH/ENTPD5 Expression Enhances the Invasiveness of Human Prostate Cancer Cells by a Protein Kinase Cδ–Dependent Mechanism

Abstract: Previous reports showed that PCPH is mutated or deregulated in some human tumors, suggesting its participation in malignant progression. Immunohistochemical analyses showed that PCPH is not expressed in normal prostate, but its expression increases along cancer progression stages, being detectable in benign prostatic hyperplasia, highly expressed in prostatic intraepithelial neoplasia, and remaining at high levels in prostate carcinoma. Experiments designed to investigate the contribution of PCPH to the malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 44 publications
(64 reference statements)
4
52
0
Order By: Relevance
“…There is also evidence that PKCd can enhance cell motility, possibly by affecting the expression and activity of b1 integrins and focal adhesion kinase (Chen et al 2007, Brenner et al 2008. Furthermore, PKCd has been shown to act to promote invasiveness in prostate and breast cancer cells (Kiley et al 1999, Kharait et al 2006, Villar et al 2007, and rottlerin has been shown to completely prevent invasion induced by the integrin-activating peptide PHSRN in DU-125 prostate cancer cells (Zeng et al 2006). We have shown that both FSH and LH induce migration in ovarian cancer cells that is dependent upon ERK1/2 and PKCd signalling.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that PKCd can enhance cell motility, possibly by affecting the expression and activity of b1 integrins and focal adhesion kinase (Chen et al 2007, Brenner et al 2008. Furthermore, PKCd has been shown to act to promote invasiveness in prostate and breast cancer cells (Kiley et al 1999, Kharait et al 2006, Villar et al 2007, and rottlerin has been shown to completely prevent invasion induced by the integrin-activating peptide PHSRN in DU-125 prostate cancer cells (Zeng et al 2006). We have shown that both FSH and LH induce migration in ovarian cancer cells that is dependent upon ERK1/2 and PKCd signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies therefore support a positive role for PKCδ in the malignant progression of tumors. Actually, elevated expression of PKCδ has been detected in certain tumors Nabha et al, 2005;Villar et al, 2007) and has been found to increase the motility and metastatic potential of tumor cells (Kiley et al, 1999; Alonso-Escolano et al, 2006;Kharait et al, 2006;Villar et al, 2007).…”
Section: Journal Of Cell Sciencementioning
confidence: 99%
“…Increasing evidence also indicates that PKCδ has a positive role in cell motility (Chen et al, 2007;Gliki et al, 2002;Iwabu et al, 2004;Li et al, 2003) and the metastatic potential of tumor cells (Kiley et al, 1999;Kruger and Reddy, 2003; Alonso-Escolano et al, 2006;Kharait et al, 2006;Villar et al, 2007). However, the role of PKCδ in intercellular junctions remains obscure.…”
mentioning
confidence: 99%
“…Previous studies have shown that invasion of prostate cancer cells (PC-3) is dependent on the activity of different PKCs, among them PKC␦ (46,49). PC-3 cells expressing Spry2 were shown to be less invasive, comparable with those cells where endogenous PKC␦ was knocked down or where the activity of endogenous PKC␦ was blocked by a kinase-dead, dominant negative PKC␦.…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer cells, PKC␦ has been shown to be important for cell invasion (46). To gain insight into the physiological relevance of this interaction, we investigated whether Spry2 could affect the invasiveness of a prostate cancer cell line, PC-3.…”
Section: Spry2 Inhibits Cell Invasion Of Pc-3 Cells-pkc␦ Has Beenmentioning
confidence: 99%